Successful Second-Line Metronomic Temozolomide in Metastatic Paraganglioma: Case Reports and Review of the Literature. (7th April 2018) - Tena, Isabel; Gupta, Garima; Tajahuerce, Marcos; Benavent, Marta; Cifrián, Manuel; Falcon, Alejandro; Fonfria, María; Olmo, Maribel del; Reboll, Rosa; Conde, Antonio; Moreno, Francisca; Balaguer, Julia; et al.
Metastatic pheochromocytoma and paraganglioma (mPHEO/PGL) are frequently associated with succinate dehydrogenase B ( SDHB ) mutations. Cyclophosphamide-dacarbazine-vincristine (CVD) regimen is recommended as standard chemotherapy for advanced mPHEO/PGL. There is limited evidence to support the role of metronomic schemes (MS) of chemotherapy in mPHEO/PGL treatment. We report 2 patients with SDHB -related mPGL who received a regimen consisting of MS temozolomide (TMZ) and high-dose lanreotide after progression on both CVD chemotherapy and high-dose lanreotide. Molecular profiling of the tumor tissue from both patients revealed hypermethylation of the O6-methylguanine-DNA-methyltransferase ( MGMT ) promoter. In one patient, progression-free survival was 13 months and the second patient remained under treatment after 27 months of stabilization of metabolic response of his disease. Treatment was well tolerated, and adverse effects were virtually absent. A modification in the scheme of TMZ from standard schemes to MS is safe and feasible and can be considered in patients with progressive mPHEO/PGL refractory to dacarbazine in standard doses.